First report of anticancer agent, lapachol producing endophyte, Aspergillus niger of Tabebuia argentea and its in vitro cytotoxicity assays - Channabasava, .; Govindappa, Melappa (Bangladesh Journal of Pharmacology, 2014)
All parts of Tabebuia argentia were used for isolation and identified the lapachol producing endophytes were used for evaluation of in vitro cytotoxicity (antimitotic, antiproliferative, determination of cell viability, DNA fragmentation). Five endophytes (leaf endophytes, Alternaria alternata, Alternaria sp., Aspegerillus niger, Penicillium sp. and the bark endophyte, A. alternata) are able to produce potent anticancer agent lapachol. The 3rd and 4th fractions of endophytic extracts (A. niger and Penicillium sp.) exhibited the pure lapachol. The 3rd fraction of A. niger lapachol strongly inhibited the Allium cepa root actively growing cells at various stages of cell cycle in antimitotic assay and the index was 22.5 mg/mL, the yeast cells were died due to toxicity and possessed the cell necrosis and they exhibited the DNA fragmentation. Present promised endophytes can be used for production of lapachol using endophyte A. niger for large scale production of lapachol within short period of time.